1986
DOI: 10.1177/014107688607900307
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Tuberculosis: Still a Problem Today

Abstract: SummaryThirty cases of abdominal tuberculosis were diagnosed over an 18-year period, 26 being in immigrants; the mean age at presentation was 33 years. There were 25 cases of tuberculous peritonitis, two of tuberculous mesenteric lymphadenitis, and one each of gastric tuberculosis, colonic tuberculosis and tuberculous ischiorectal abscess. The presenting symptoms were of vague ill-health and not diagnostic, and the most common findings were ofpyrexia, abdominal tenderness and ascites. The most common haematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 15 publications
4
35
0
Order By: Relevance
“…Surgical treatment is reserved for complications such as intestinal obstruction and bowel perforation with peritonitis. 9,13 The aims of surgery are mainly to remove the focus of the disease and treat the mechanical effects which are causing the presenting morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment is reserved for complications such as intestinal obstruction and bowel perforation with peritonitis. 9,13 The aims of surgery are mainly to remove the focus of the disease and treat the mechanical effects which are causing the presenting morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Finding of abdominal tenderness in present study is comparable with study by Safarpor Faizollah et al 1 In the present study, association of old pulmonary TB with abdominal TB was found in 16.12% patients which comparable with study by Rai et al and more than in study by Ramesh J et al while family history of pulmonary TB or treatment for pulmonary TB in family member was found in 22.58% patients with abdominal TB which is comparable with study by Rai et al 3,5 In the present study, 68.41% patients had normocytic normochromic anemia which is comparable to study by Wells AD et al and Ramesh J et al while 28% patients showed raised TLC count which is comparable with Islam J et all . 5,29,30 The chest radiographs of only 8 patients (21.05%) were suggestive of tuberculosis with pulmonary infiltrates, though sputum cultures were negative in all 10 patients; a percentage one fourth of that reported in studies by Nafeh et al and Ramesh J et al 13,5 Ultrasonography of abdomen was suggestive of tuberculosis in all patients, but histology/CBNAAT results were positive in 25 patients. Though the sensitivity of CT scan was high (96%), the specificity was very low (46.15%) in our series.…”
Section: Discussionmentioning
confidence: 85%
“…ascites, gut wall thickness, lymphadenopathy, abscess, and organomegally were detected in 82% of patients. 29 Caseating lymph nodes with hypodense centres and peripheral rim enhancement along with calcification are highly suggestive of tuberculosis. 2 Histology for tuberculosis was positive in 71.42% of patients with high ESR which is comparable with study by Islam J et all.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations